Interactive Comic Video Media in Solar System Material Science Content for Grade VI Elementary School - I Made Raditya Iswanta; Kadek Suranata; Kadek Yudiana (International Journal of Elementary Education, 2025)
Science learning in elementary schools needs to be implemented innovatively to foster students’ learning interest and enhance their conceptual understanding. However, the delivery of science material is often dominated by conventional and monotonous methods, causing students to experience difficulties in understanding scientific concepts due to the language and presentation being less engaging. This study aims to analyze and develop an interactive comic video medium on the solar system topic as a valid and practical learning tool to strengthen students’ comprehension of science concepts. This research employs a Research and Development (R&D) approach using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, and sixth-grade elementary school students. Data were collected using a non-test questionnaire instrument and analyzed through descriptive qualitative and quantitative techniques. The findings indicate that the developed interactive comic video obtained excellent evaluations from both material and media experts in terms of content accuracy and visual design quality. The results of student trials also show that the media is user-friendly, engaging, and effective in helping students understand the solar system comprehensively. Thus, the interactive comic video is considered valid, practical, and feasible for continuous use in science learning. The implication of this research is that visual and narrative-based media, such as comic videos, can serve as innovative alternatives for teachers to create more contextual, enjoyable, and student-centered learning experiences in the classroom.